1993
DOI: 10.1007/bf03348848
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ipriflavone administration on bone mass and metabolism in ovariectomized women

Abstract: The aim of the present study was to assess the effects of ipriflavone administration in the prevention of the rapid bone loss that follows ovariectomy in women. After 10-30 days from bilateral ovariectomy, patients received either the sole calcium supplementation (500 mg/day, n = 16) or ipriflavone (600 mg/day, n = 16) in addition to the same daily calcium supplement for 12 months. In calcium-treated subjects urinary hydroxyproline excretion, serum alkaline phosphatase and plasma bone Gla protein levels showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…The increase in bone resorption markers preceding the increase in bone formation markers is consistent with the results of earlier cross-sectional studies (25-28) and longitudinal studies with biochemical markers other than PICP and ICTP (15,16), and this finding supports the general concept that the loss of skeletal balance shortly after acute estrogen deficiency is due to the prevalence of bone resorption over new bone deposition (29). Our results, however, clearly demonstrated a gradual decline in bone resorption after 6 months P0.…”
Section: Changes In Lumbar Bmdsupporting
confidence: 89%
See 1 more Smart Citation
“…The increase in bone resorption markers preceding the increase in bone formation markers is consistent with the results of earlier cross-sectional studies (25-28) and longitudinal studies with biochemical markers other than PICP and ICTP (15,16), and this finding supports the general concept that the loss of skeletal balance shortly after acute estrogen deficiency is due to the prevalence of bone resorption over new bone deposition (29). Our results, however, clearly demonstrated a gradual decline in bone resorption after 6 months P0.…”
Section: Changes In Lumbar Bmdsupporting
confidence: 89%
“…Furthermore, changes in bone metabolism after oophorectomy have been reported in previous studies by using serum BGP levels and/or bone alkaline phosphatase activity as indices of bone formation and urinary hydroxyproline excretion and/or plasma tartrate-resistant acid phosphatase as indices of bone resorption (15,16). The details of changes in serum PICP and ICTP in a longitudinal study, however, have never been reported.…”
mentioning
confidence: 92%
“…Ipriflavone per se has been shown to exert beneficial effects on the osteopenia induced in women by either iatrogenic [2] or physiological estrogen deficiency [1,3]. Nevertheless, it is well documented that dietary flavonoids alter the hormonal status of premenopausal women [12].…”
Section: Discussionmentioning
confidence: 99%
“…First clinical trials indicate that the compound exerts a beneficial effect in osteopenic diseases [1][2][3]. It is not clear yet whether ipriflavone acts primarily by inhibiting bone resorption or by stimulating bone formation.…”
mentioning
confidence: 99%
“…Several therapeutic agents, such as bisphosphonate, calcium, vitamin D3, vitamin K, estrogen, ipriflavon, and calcitonin, have been used for the treatment of osteoporosis ( Black et al, 1996;Gambacciani et al, 1993;Iketani & Kiriike, 2003;Recker et al, 1996;Rico, Hernandez, Revilla, & GomezCastresana, 1992). Although estrogen deficiency has been considered to be an important etiologic contributor to bone loss in AN, the effect of estrogen treatment for patients with AN is currently inconclusive ( Klibanski, Biller, Schoenfeld, Herzog, & Saxe, 1995;Kreipe, Hicks, Rosier, & Puzas, 1993;Maugars et al, 1996;Seeman, Szmukler, Formica, Tsalamandris, & Mestrovic, 1992).…”
Section: Resultsmentioning
confidence: 99%